PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJEMEN DAN SENJANGAN ANGGARAN: SYSTEMATIC LITERATURE REVIEW - Jelang Romadhan, Fais Bagus; Rusmana, Oman (JURNAL ILMIAH EDUNOMIKA, 2024)
Budget participation is a process in which the individuals involved have an influence on the budget targets to be achieved. Participatory budgeting is expected to improve employee performance and reduce budgetary slack. The purpose of this study is to determine the distribution of articles, theories, and methodologies used in research on the relationship between budgetary participation with management performance and budgetary slack. A systematic literature review was used as the analytical method. The unit of analysis in this study is 21 journal articles that discuss the relationship between budgetary participation with management performance and budgetary slack. Articles are selected through a series of categories. The results of the research show that motivation theory and agency theory are the most frequently used theories in budgetary participation research. Then, the majority of budget participation researchers used a quantitative approach with survey techniques in their research. Keywords: Budget participation, Performance management and Budgetary slack